Jaran Mbako - Laras Wiswalendya; Silvester Pamardi (Universitas Trunodjoyo Madura, 2023)
Jaran Mbako is on a journey, a form of survival and enthusiasm to maintain tobacco farming amid the problems experienced by tobacco farmers in Temanggung. rising tobacco prices, restrictions on supply in factories, uncertain seasons, fraudulent collectors, and anti-smoking advertisements that continue to be broadcast everywhere. The problems that arose made them more aggressive in fighting and maintaining tobacco farming. Because with tobacco, they can live. Tobacco is their breath. This study aims to determine the importance of tobacco farming among the people of Temanggung. The method used is the creation method with the principles of re-visiting, re-questioning, and re-interpreting with data collection techniques using an ethnographic approach. The results of this study are dance films based on motion, which are strengthened by editing and camera and audio details. Jaran movement as an inspiration and a symbol of strength and life Horses will live under any circumstances, just like tobacco farmers will live under any circumstances